A new class of magnetorheological elastomers based on waste tire rubber and the characterization of their properties. (4th October 2016) - Ubaidillah,; Imaduddin, Fitrian; Li, Yancheng; Mazlan, Saiful Amri; Sutrisno, Joko; Koga, Tsuyoshi; Yahya, Iwan; Choi, Seung-Bok
Abstract: This paper proposes a new type of magnetorheological elastomer (MRE) using rubber from waste tires and describes its performance characteristics. In this work, scrap tires were utilized as a primary matrix for the MRE without incorporation of virgin elastomers. The synthesis of the scrap tire based MRE adopted a high-temperature high-pressure sintering technique to achieve the reclaiming of vulcanized rubber. The material properties of the MRE samples were investigated through physical and viscoelastic examinations. The physical tests confirmed several material characteristics—microstructure, magnetic, and thermal properties–while the viscoelastic examination was conducted with a laboratory-made dynamic compression apparatus. It was observed from the viscoelastic examination that the proposed MRE has magnetic-field-dependent properties of the storage modulus, loss modulus, and loss tangent at different excitation frequencies and strain amplitudes. Specifically, the synthesized MRE showed a high zero field modulus, a reasonable MR effect under maximum applied current, and remarkable damping properties.